The Too-Much-Talent Effect: Team Interdependence Determines When More Talent Is Too Much or Not Enough - Swaab, Roderick I.; Schaerer, Michael; Anicich, Eric M.; Ronay, Richard; Galinsky, Adam D. (Psychological Science, 2014)
Five studies examined the relationship between talent and team performance. Two survey studies found that people believe there is a linear and nearly monotonic relationship between talent and performance: Participants expected that more talent improves performance and that this relationship never turns negative. However, building off research on status conflicts, we predicted that talent facilitates performance—but only up to a point, after which the benefits of more talent decrease and eventually become detrimental as intrateam coordination suffers. We also predicted that the level of task interdependence is a key determinant of when more talent is detrimental rather than beneficial. Three archival studies revealed that the too-much-talent effect emerged when team members were interdependent (football and basketball) but not independent (baseball). Our basketball analysis also established the mediating role of team coordination. When teams need to come together, more talent can tear them apart.